Critical Analysis: Education Quality Management - Rahmad Nasir; Cepi Safruddin Abdul Jabar (The Indonesian Institute of Science and Technology Research, 2022)
Conceptually there are many definitions of quality from experts who originally came from the industrial world to be adopted in education. Various purposes of quality include customer satisfaction, conformity to specifications, and continuous improvement. Quality management is used in education through management functions such as quality planning, quality implementation, quality control and evaluation. Quality standards have been set as ideal regulations to become a quality assessment measure in education. This article aims to examine the basic concepts of quality and quality management and compare their application in Indonesia. Technical differences in the implementation of quality management through the stages in each institution still provide the same substance, namely quality management, which is always based on regulatory standards or certain theoretical concepts. These stages are linear with general management functions such as quality planning, quality implementation and quality control/ evaluation.